The plastics treaty: steps forward, agreement deferred - Guo, Jianping; Hu, Rui (Frontiers in Marine Science, 2025)
The United Nations Environment Assembly (UNEA) and the Intergovernmental Negotiating Committee (INC) have been working on an international legally binding instrument on plastic pollution, including in the marine environment (Plastics Treaty) since 2022. This piece presents a perspective on the current progress of the Plastics Treaty from the first session of the UNEA to the last session of the INC as of August 2025, highlighting different positions of States and groups of States, based on which, argues that some of the key contentions remain throughout the negotiations.